The Effectiveness of Psychodrama Program Training on Resilience and Psychological Capital in Women with Breast Cancer - Raoufi, Mehri; Seyrafi, Mohammad Reza; Ahadi, Hasan (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was to determine the effect of psychotherapy program training on resilience and psychological capital of breast cancer women in Bandar Abbas. Methods: This experimental study was performed with a pretest and posttest design with a control group. The statistical population of this study consisted of all women with breast cancer in Shahid Mohammadi Hospital in Bandar Abbas, whose number was 78 people. Of these, 60 women with breast cancer in Bandar Abbas in 2019 who had the same severity and level of the disease, were selected by convenience sampling, were divided into two groups of intervention and control. The instruments used were Luthans (2007) Psychological Capital Questionnaire and Connor & Davidson (2003) Resilience Scale. The validity and reliability of these tools have been investigated in previous studies. Psychoanalytic training sessions based on the Leventon protocol (2009) were held in nine sessions, ninety minutes in a month. Questionnaires were completed in the first and ninth stages of the intervention. Data analysis was performed using SPSS.22 software. Results: Psychotherapy program training increased resilience (F= 199.71, P<0.001) and also psychological capital (F= 10.80, P<0.001) of patients with breast cancer. Conclusion: Psychotherapy program training method helps cancer patients in various ways, increasing resilience and psychological capital.